The Influence of Workload, Organizational Culture and Extrinsic Motivation on Employee Performance - Muhamad Raffi Ferdian; Hasan (Universal Business and Management Review, 2026)
This study aims to analyze the effect of workload, organizational culture, and extrinsic motivation on employee performance at PT Decalling Media Internusa. This research employed a quantitative method using a saturated sampling technique involving 52 employees. The data were analyzed using multiple linear regression and t-tests. The results indicate that workload, organizational culture, and extrinsic motivation each have a positive and significant effect on employee performance. Further findingdescribe these variables collectively explain 56.4% of the variation in employee performance.